Influence of joint kinematics on polyethylene wear in anatomic shoulder joint arthroplasty - Braun, Steffen; Schröder, Stefan; Müller, Ulrike; Sonntag, Robert; Bülhoff, Matthias; Kretzer, Jan Philippe (Journal of shoulder and elbow surgery, 2018)
Background - Despite the positive results in total shoulder arthroplasties (TSAs), a higher revision rate is documented compared with total hip and knee replacements. Wear is the possible main cause of TSA failure in the long-term. This study investigated the effect of joint kinematics and the influence of the rotator cuff on the polyethylene wear performance in an anatomic TSA. - Methods - Lifting a load of 2 kg with an abduction/adduction of 0° to 90° was simulated for 2 × 106 cycles as a primary motion using a fully kinematic joint simulator. A combined rotation in anteversion-retroversion of ±5° and ±10° was also simulated. The force in the superior-inferior direction and the axial joint compression were applied under force control based on in vivo data of the shoulder. A soft tissue restraint model was used to simulate an intact and an insufficient rotator cuff. - Results - The highest wear rate in the intact rotator cuff group was 58.90 ± 1.20 mg/106 cycles with a combined rotation of ±10°. When an insufficient rotator cuff was simulated, the highest polyethylene wear rate determined was 79.67 ± 4.18 mg/106 cycles. - Conclusions - This study confirms a high dependency of the polyethylene wear behavior and dimension on the joint kinematics in total shoulder replacement. This can be explained by an increasing cross-shear stress on the polyethylene component. The results obtained indicate that additional combined kinematics are an indispensable part of wear tests on anatomic shoulder replacements.
Gesehen am 06.08.2019